Islam and cultural dialectic: A main narrative of positioning Gorontalo on the Spice Route - Nensia; Lamijo; Hamsiati; Abd. Rahman Hamid; Idham; Abu Muslim; Muhammad Nur Ichsan Azis (Masyarakat, Kebudayaan dan Politik, 2026)
The province of Gorontalo, Indonesia, has long been a destination for diverse ethnic groups arriving through maritime trade. Though often mentioned in articles and official sources as one of key contributors to the archipelagic spice route, no research has identified Gorontalo as a spice-producing region. Moreover, the Indonesian Ministry of Education and Culture has a long-term national program called, “Jalur Rempah,” which includes several maritime route points including the Gorontalo spice route. Thus, this study sought to discover why Gorontalo served as an important node on the spice route leading to how Islamic encounters and cross-cultural exchanges shaped its society. Using qualitative methods including in-depth interviews, observation, and literature review with historical and synchronic approaches, this research found that Gorontalo’s spice route functioned not only as a channel for commodities but also for ideological and cultural exchange. In this case, Islamic kingdoms such as Ternate, Gowa, and Bone played vital roles in spreading Islamic teachings. Moreover, Gorontalo’s cultural arts evolved under the influence of religion and foreign cultures, reflecting the region’s openness and deep respect for guests. From these characteristics, this study demonstrates Gorontalo’s unique adaptability to global interactions along the spice route and contributes to reinforcing the recognition of the spice route as a world cultural heritage.